SELECTED PROPERTIES OF CONTEMPORARY ENDODONTIC SEALERS: PART 2 - M Rosa; Y Morozova; R Moštěk; A Jusku; V Kováčová; L Somolová; I Voborná; T Kovalský (Czech Dental Chamber, 2021)
Introduction and aims: Materials intended for the definitive filling of root canals form an integral part of the equipment of every dentist's office, and may differ in some of their physical, chemical and biological properties, depending on their composition. Where some materials excel in their properties, others have serious shortcomings and, conversely, what individual manufacturers try to overcome by modifying their composition, or bring to market materials based on a different, new basis. However, this further complicates the already complex clarity between the individual types of materials. Clinicians often face the difficult task of choosing from such a wide and complicated range of materials one that would meet their requirements for workability, stability, biocompatibility, antibacterial action and, last but not least, the financial complexity of subsequent treatment. The purpose of this article is to help clinicians in the orientation between the different types of materials used in current endodontics to definitively fill the root canal and also to facilitate the selection of the ideal material for their practice. In the first part of this article, attention was paid to conventional and more traditional materials based on calcium hydroxide, zinc oxideugenol and the gold standard in endodontics, materials based on polyepoxide resins, discussing properties such as setting time, their solidification pH, radiopacity, solubility and susceptibility. to the formation of root filling leaks over time, volume changes occurring during and after solidification of these materials, cytotoxicity, antibacterial properties and the ability of these materials to stain hard dental tissues over time. Materials, methods: The second part of the article deals with materials based on methacrylate resins, silicones and in the end attention is focused on the latest trend of current endodontics - bioceramic materials. By comparing the properties of the individual materials to which this part of the article is devoted, it can be said that methacrylate sealers have mild antibacterial properties, do not stain hard dental tissues, but also show a slight susceptibility to leaks and medium to high cytotoxicity. Silicone- -based sealants, in turn, are characterized by excellent biocompatibility, low tendency to discolor hard tooth tissue, minimal solubility in tissue fluids, and also very little tendency to leak, but their antibacterial properties are negligible or non-existent. The new, bioceramic materials excel in particular with excellent antibacterial properties, low solubility and susceptibility to leaks, as well as a low risk of staining of hard dental tissues, but they also show a certain degree of cytotoxicity.